Red Alert! Unveiling Insights in Violence Against Women through Interactive Data Visualization - Gabriel Zurawski; Vinícius Pedroso; Eduarda Patricio; Giovanna Castro; André F. Rollwagen; Isabel H. Manssour (Journal on Interactive Systems, 2025)
Governments nowadays make several open data sets available, including data on reports of violence against women. Such a type of violence is considered a public health and safety problem and requires approaches that help identify behavioral patterns, trends, and profiles of victims and perpetrators. The analysis of this type of data can be facilitated with the use of interactive visualization. Visual representation techniques enable the identification of patterns and trends, providing insights that aid decision-making. Given this context, this paper proposes using interactive visualization techniques to explore government data on violence against women, aiming at a better understanding and preventive actions. Data obtained from the Women’s Service Center (Call 180) can be explored through a set of dashboards called MARIA (Mapping and Analysis of Risks and Insights on Abuse Against Women), which reveal hidden insights and patterns, helping to identify vulnerabilities. The purpose is to foster more knowledge about this data to develop strategies to prevent and combat violence against women. Interviews with domain experts have shown that MARIA is easy to use, contributes to data knowledge, and provides insights consistent with reality.